Correction: Steatosis is involved in the progression of kidney disease in a high-fat-diet-induced non-alcoholic steatohepatitis mouse model. - PLOS One Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0265461.].